(untitled) (Indian Journal of Child Health, 2019)
Background: Type 1 diabetes (T1D) is a chronic childhood disorder and is likely to be associated with dyslipidemia. Vitamin D deficiency further increases the risk of dyslipidemia; Vitamin D is believed to have cardioprotective properties. Objectives: The objective of this study was to study the effect of Vitamin D supplementation on lipid profile and glycemic control (hemoglobin A1c [HbA1c]) in children with T1D. Materials and Methods: A prospective, non-blinded, single-arm, supplementation study was performed in 145 underprivileged children with T1D from 2015 to 2017. Anthropometry, biochemical parameters (HBA1c, Vitamin D, and lipid parameters) were assessed at baseline. Children were supplemented with 1000 IU Vitamin D and 500 mg calcium daily. Follow-up data at the end of 1 year of supplementation were recorded. Results: The mean age at presentation of T1D in children was 12.5±3.9 years (65 boys). Baseline HbA1c, cholesterol, and Vitamin D were 10.3±2.1%, 4.1±1.1 mmol/L, and 33.6±18.5 nmol/L, respectively. At end line, HbA1c, cholesterol, and Vitamin D were 9.4±1.7%, 3.3±0.8 mmol/L, and 51.1±21.8 nmol/L, respectively (p<0.05 for all). Regression analysis showed that increase in Vitamin D was associated with improvement in cholesterol and HbA1c (p<0.05). Conclusion: Daily supplementation with Vitamin D along with calcium in children with T1D results in improvement in lipid profile and glycemic control.